2018
DOI: 10.3390/ijms19041074
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage Populations in Visceral Adipose Tissue from Pregnant Women: Potential Role of Obesity in Maternal Inflammation

Abstract: Obesity is associated with inflammatory changes and accumulation and phenotype polarization of adipose tissue macrophages (ATMs). Obese pregnant women have alterations in adipose tissue composition, but a detailed description of macrophage population is not available. In this study, we characterized macrophage populations in visceral adipose tissue (VAT) from pregnant women with normal, overweight, and obese pregestational weight. Immunophenotyping of macrophages from VAT biopsies was performed by flow cytomet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 55 publications
0
10
0
Order By: Relevance
“…There was evidence of a heterogeneous response where, when those who had gestational weight loss were excluded, obese women showed an increase in adipocyte number [38]. Third trimester SAT [39,40] and VAT [41] adipocyte hypertrophy has also been reported in obese compared to lean third trimester pregnant women. Others have reported that obese women had fewer adipocytes and increased evidence of necrosis and apoptosis suggesting a higher adipocyte turnover and greater adipose tissue remodelling compared to lean pregnant women [39].…”
Section: Adipocyte Function In Lean and Obese Pregnancymentioning
confidence: 99%
“…There was evidence of a heterogeneous response where, when those who had gestational weight loss were excluded, obese women showed an increase in adipocyte number [38]. Third trimester SAT [39,40] and VAT [41] adipocyte hypertrophy has also been reported in obese compared to lean third trimester pregnant women. Others have reported that obese women had fewer adipocytes and increased evidence of necrosis and apoptosis suggesting a higher adipocyte turnover and greater adipose tissue remodelling compared to lean pregnant women [39].…”
Section: Adipocyte Function In Lean and Obese Pregnancymentioning
confidence: 99%
“…CD11b expression was reported to be elevated in obese individuals which associated with the development of metabolic syndrome 34 . CD11c expression was found to be higher in adipose-resident HLA-DR + macrophages from obese women 35 . Since TNF-α is invariably elevated in obesity and metabolic syndrome, expression of inflammatory phenotypic markers in monocytes/macrophages could have been induced by TNF-α.…”
Section: Discussionmentioning
confidence: 86%
“…CD11b expression was reported to be elevated in obese individuals which associated with the development of metabolic syndrome 26 . CD11c expression was found to be higher in adipose-resident HLA-DR⁺ macrophages from obese women 27 . Since TNF-α is invariably elevated in obesity and metabolic syndrome, expression of inflammatory phenotypic markers in monocytes/macrophages could have been induced by TNF-α.…”
Section: Discussionmentioning
confidence: 87%